7.5-y-2-(7.5-y-2)⋅0.4=1.8

Simplify each term.

Subtract 2 from 7.5.

7.5-y-2-(-y+5.5)⋅0.4=1.8

Apply the distributive property.

7.5-y-2+(–y-1⋅5.5)⋅0.4=1.8

Multiply –y.

Multiply -1 by -1.

7.5-y-2+(1y-1⋅5.5)⋅0.4=1.8

Multiply y by 1.

7.5-y-2+(y-1⋅5.5)⋅0.4=1.8

7.5-y-2+(y-1⋅5.5)⋅0.4=1.8

Multiply -1 by 5.5.

7.5-y-2+(y-5.5)⋅0.4=1.8

Apply the distributive property.

7.5-y-2+y⋅0.4-5.5⋅0.4=1.8

Move 0.4 to the left of y.

7.5-y-2+0.4⋅y-5.5⋅0.4=1.8

Multiply -5.5 by 0.4.

7.5-y-2+0.4y-2.2=1.8

7.5-y-2+0.4y-2.2=1.8

Simplify by adding terms.

Subtract 2 from 7.5.

-y+5.5+0.4y-2.2=1.8

Add -y and 0.4y.

-0.6y+5.5-2.2=1.8

Subtract 2.2 from 5.5.

-0.6y+3.3=1.8

-0.6y+3.3=1.8

-0.6y+3.3=1.8

Subtract 3.3 from both sides of the equation.

-0.6y=1.8-3.3

Subtract 3.3 from 1.8.

-0.6y=-1.5

-0.6y=-1.5

Divide each term in -0.6y=-1.5 by -0.6.

-0.6y-0.6=-1.5-0.6

Cancel the common factor of -0.6.

y=-1.5-0.6

Divide -1.5 by -0.6.

y=2.5

y=2.5

Solve for y 7.5-y-2-(7.5-y-2)*0.4=1.8